Role of taste genetic variations in sweet, fatty and sweet- fatty taste perception and food intake amongst obese and non-obese Malay adults in Malaysia - Bahauddin, Ahmad Riduan (2019)
The genetic variation of taste could explain the variations observed in human perceptions and predict individuals’ food choices and intake. However, the current understanding of how taste genetic could affect individual’s taste function and perception in various food systems and their relationship towards dietary intke is limited. Thus, the study was conducted to examine the effects of genetic variation on taste (in terms of taste of receptor polymorphism and Propylthiouracil (PROP) status on sweet and / or fat perceptions of different food models and also food intake between obese and obese subjects. A total of 88 obese subjects (means age of 27.6 ± 6.24 years and BMI of 33.46 ± 3.60 kgm2) and 92 non-obese subjects (means age of 25.86 ± 5.28years and BMI of 21.79 ± 2.35 kgm2) were genotyped for TAS1R2 gene at rs35874116, rs9701796, and rs12033832, TAS1R3 gene at rs307355, rs35744813), CD36 gene at rs1761667, rs1527483, and rs1049673 and TAS2R38 gene at rs613798. PROP taster status (e.g. supertaster, medium taster and non-taster) were determined using paper disk rating. Three type of samples namely blank taste solution (sweet taste - sucrose solution; fatty taste (oiliness) - linoleic acid solution), singular taste food (sweet – rose flavored pudding; fatty (creaminess) – ‘bubur chacha’) and binary taste food (sweet-fatty taste – ‘bubur chacha’) were evaluated for taste intensity and hedonic responses using general Labelled Magnitude scale (gLMS) and general Labeled Hedonic Scale (gLHS). Subjects completed 3 days food record (2 weekdays, 1 weekend) and 2 set of food frequency questionnaires (sweet food and fatty food) to assess their habitual food consumption and dietary intake. Overall, there are significant differences in term of weight and BMI between obese and non-obese subjects. In contrast, no significant differences was found on socio demographic characteristic variables between both groups. Obese and non-obese subjects did not differ on the sweetness, oiliness and creaminess rating of tasting samples except for binary taste food, the ‘bubur chacha’. rs12033832 of TAS1R2 gene and rs1761667 of CD36 gene was associated with taste intensity and liking rating of blank solution and single taste food but not in sweet-fatty mixtures in both obese and non-obese subjects. Individuals with AA genotype for both genes perceived greater taste intensity rating and give lower liking rating of tasting samples. In contrast, PROP taster status was associated with taste intensity and liking rating of all type of samples. Regardlesss of BMI status, supertaster rated higher taste intensity and had lower mean liking ratings in most of samples. BMI status and PROP taster status seem to play a role in sweet-fatty taste optimal preference. Non-taster - obese subjects preferred higher fat content (8.75%) in stimuli compared to only 6.6% of fat in supertaster – non-obese subjects. Assessment of dietary intake revealed that obese subjects differed significantly on energy and protein intake compared to nonobese subjects. No significant difference was observed among PROP taster status on the subject’s habitual sweet or fatty food consumption for both BMI groups. In conclusion, taste receptor gene variant was shown to be responsible for the variation of individuals’ taste sensitivity but are not related to taste liking and food intake. Furthermore, the influence of taste receptor gene variances on perception was demolished as the stimuli become more complex (e.g binary taste system). Thus, it can be concluded that taste receptor gene variances and PROP taster status did not seem to play a major role in human taste perception and food intake among obese and non-obese subjects.